3d imaging of soft-tissue samples using an x-ray specific staining method and nanoscopic computed tomography - Busse, Madleen; Mueller, Mark; Kimm, Melanie; Ferstl, Simone; Allner, Sebastian; Achterhold, Klaus; Herzen, Julia; Pfeiffer, Franz (Journal of Visualized Experiments, 2019)
We demonstrate a laboratory-based method combining X-ray microCT and nanoCT with a specific X-ray stain, which targets the cell cytoplasm. The described protocol is easy to apply, fast and suitable for larger soft-tissue samples. The presented methodology enables the characterization of crucial tissue structures in three dimensions and is demonstrated on a whole mouse kidney. The multiscale approach allows to image the entire mouse kidney and supports the selection of further volumes of interest, which are acquired with higher resolutions ranging into the nanometer range. Thereby, soft-tissue morphology with a similar detail level as the corresponding histological light microscopy images is reproduced. Deeper insights into the 3D configuration of tissue structures are achieved without impeding further investigations through histological methods.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D imaging; Bioengineering; Cytoplasm-specific staining; Eosin stain; High-resolution; Issue 152; Microscopic X-ray computed tomography; Microstructure; Multiscale imaging; Nanoscopic X-ray computed tomography; Nondestructive; Soft tissue imaging; X-ray staining method